SOCIOCULTURAL MISSION OF THE UNIVERSITY IN THE CONTEXT OF THE REGION DEVELOPMENT - Dmitry N. Bezgodov; Oksana I. Belyaeva (Moscow Polytechnic University, 2016)
The article explores the role of the University in creating an auspicious sociocultural environment that is conducive to solution of topical Russian problem of single-industry towns. The authors consider some specific forms of work, projects, initiatives of the Ukhta State Technical University, which promote socio-economic development of the city and the region.